2007
DOI: 10.1016/j.ejheart.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aldosterone receptor blockade in patients with mild–moderate heart failure taking a beta‐blocker

Abstract: Aims: Spironolactone improves prognosis in severe heart failure (HF). We investigated its effects in patients with mild-moderate HF treated with an ACE inhibitor and beta-blocker. Methods and results: Randomised, double-blind, parallel-group, 3-month comparison of placebo and spironolactone (25 mg daily) in 40 patients in New York Heart Association (NYHA) class I (20%), II (70%) or III (10%), with a left ventricular ejection fraction of b 40%.The mean (standard error) changes from baseline in the spironolacton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 35 publications
2
32
0
1
Order By: Relevance
“…In a 40-patient randomized trial of 3 months duration, Berry et al 17 found that spironolactone improved BNP and PIIINP levels compared with placebo but had unfavorable effects on a quality-of-life measure and on serum creatinine. Chan et al 18 reported on 51 patients with mild-to-moderate HF, 70% of whom were on BBs.…”
Section: Discussionmentioning
confidence: 99%
“…In a 40-patient randomized trial of 3 months duration, Berry et al 17 found that spironolactone improved BNP and PIIINP levels compared with placebo but had unfavorable effects on a quality-of-life measure and on serum creatinine. Chan et al 18 reported on 51 patients with mild-to-moderate HF, 70% of whom were on BBs.…”
Section: Discussionmentioning
confidence: 99%
“…It is the inactive split product of the BNP [22]. NT-proBNP levels often decline after initiation and up-titration of HF therapy such as vasodilators and aldosterone blockers [23][24][25]. Persistently elevated (or rising) levels of NT-proBNP are predictive of poor outcome [26].…”
Section: Discussionmentioning
confidence: 99%
“…De ce fait, en dépit des nombreuses publications faisant état d'altérations de ces marqueurs dans les maladies cardiaques responsables de la survenue d'une fibrose ou de la destruction du réseau de collagène au niveau du myocarde, seuls quelques uns d'entre eux satisfont à cette exigence et apportent donc des informations quant à leur utilité clinique potentielle (Tableau 4 [20][21][22][23][24][25][28][29][30][31]40,[61][62][63][64][65][66][67][68] ). Il est à noter que certaines de ces études font état d'altérations intéressant plus d'un biomarqueur, ce qui permet d'envisager l'emploi combiné de plusieurs marqueurs afin de recueillir davantage de renseignements sur les perturbations du métabolisme du collagène dont il est ici question.…”
Section: Aspects Liés à L'analyse Coût/bénéficeunclassified
“…For instance, it has been reported that serum PICP decreases in hypertensive patients being treated with angiotensin type 1 receptor antagonists 28,[61][62][63][64] or HF patients treated with the loop diuretic torasemide, 27,29 PIIINP decreases in HF patients treated with aldosterone antagonists, [65][66][67][68] CITP and MMP-1 increase in hypertensive patients treated with angiotensin-converting enzyme inhibitors, 69,70 and CITP decreases in hypercholesterolemic patients treated with statins. 71 Thus, the potential influence of previous pharmacological treatment must be carefully considered in studies assessing serum biomarkers of collagen metabolism in cardiac patients.…”
Section: Aspects Related To the Effects Of Pharmacological Treatmentmentioning
confidence: 99%